The hybrid algorithms in constrained optimization of the permanent magnet motors - Łukasz Knypiński; Ramesh Devarapalli; Frederic Gillon (IET Science, Measurement & Technology)
Abstract Here, different hybrid optimization algorithms have been applied to the constrained optimization of the line‐start permanent magnet synchronous motor. The optimal results for the hybrid Cuckoo Search and hybrid Grey Wolf Optimization have been compared. In the primary objective function, the parameters describing motor functional parameters in the steady state have been included. Moreover, the non‐linear constraint function has been taken into account. The optimization procedures have been elaborated in the Delphi and Matlab environments. The mathematical model of the line‐start permanent magnet motor has been developed in the Maxwell environment. Selected optimization results are presented and discussed.